Behavior of woven fabric composite under tensile loads in different directions using acoustic emission. (20th July 2022) - Dehnad, Milad; Dolatabadi, Mehdi Kamali; Najafabadi, Mehdi Ahmadi; Asgharian Jeddi, Ali Asghar
The woven fabric composites were used in different industries for their special specification. This study aimed to address failure mechanisms in single-layer woven fabrics. The acoustic emission (AE) technique and wavelet transform were used for composite structural health monitoring and failure rate evaluation. From a mechanical study viewpoint, the load-displacement behavior of plain-woven glass composite was examined under tension in the principal directions (0 and 90°) and off-axis (30, 45, and 60°). The results indicated that off-axis samples are deformed and curled due to the slippage and rotation of warp and weft yarns. The mechanical measurements were synchronized with the AE data in an acousto-mechanical study. The load-displacement behavior of samples was zoned out with two criteria: frequency and energy. Eventually, three failure modes were identified: matrix damage, interface damage, and fiber breakage. The results showed that events with a frequency above 400 kHz at different angles could be attributed to fiber breakage. Also, the applied force angle effectively affects the type of fiber failure (tensile and shear failure). It was found that in addition to tensile failure, shear failure also increases sharply by increasing the angle between the main directions. So that the maximum number of shear fiber failures occurred at the angle of 45° between the main directions. On the off-axis, the number of fibers exposed to the load also increased, increasing the number of breakages.